Differences in joint movements of skilled and unskilled players during basketball three-point shots - Tanabe, S.; Seto, T.; Kawabata, K.; Murakami, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
The purpose of this study was to clarify differences in the joint movements of skilled and unskilled players during basketball three-point shots. Thirty male collegiate basketball players (skilled players) and thirty male college students who did not technically play basketball (unskilled players) participated. The three-dimensional coordinates of reflective markers attached to the subjects and the basketball while performing three-point shots were obtained using a motion capture system with 22 cameras (250 fps). The findings are summarized as follows. 1) The height of the ball at release was significantly greater for the skilled players than for the unskilled players. However, the initial ball velocity and angle of ball projection were significantly greater for the unskilled players than for the skilled players. 2) Both the skilled and unskilled players produced large angular velocities of elbow extension, which resulted in high ball velocities. However, the movements of skilled players were more efficient, generating higher ball velocities with smaller angular velocities. 3) While both the skilled and unskilled players used wrist palmar flexion and finger movement to accelerate the ball, the unskilled players used significantly more wrist palmar flexion, whereas the skilled players used significantly more finger movement to produce the ball velocities. 4) Shoulder abduction and finger movement worked to develop the vertical ball velocity to maintain the appropriate angle of ball projection.